Testing causal relation among central and eastern European equity markets: evidence from asymmetric causality test - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
The aim of this study is to analyse the presence of a causal link among financial markets of Central and Eastern Europe (CEE) countries by adopting an asymmetric causality test. The standard causality test results suggest a causal relation running from the Czech Republic to Poland. Also, the Poland stock market is found to be a Granger cause of Turkey stock markets. Asymmetric causality test results indicate only a causal link going from the Czech Republic to Hungary and Poland. In addition, the presence of financial integration between Germany and CEE equity markets cannot be determined.
Keywords: Stock markets; financial integration; causality; CEE equity markets; UNIT-ROOT HYPOTHESIS; OIL-PRICE SHOCK; STOCK MARKETS; GREAT CRASH